COMPARATIVE ANALYSIS OF PRODUCT PLACEMENT USING MEDIA TELEVISION ON BUYING DECISION BETWEEN YOUNG FEMALE AND ADULT FEMALE - Arbie, Inayah; Pandowo, Merinda (Sam Ratulangi University, 2015)
ABSTRACT Product placement is an advertising technique used by companies to subtly promote their products through a non-traditional advertising technique, usually through appearances in film, television, or other media. It will get a lot of attention to their product placement on consumer’s mind. Through product placement, company expects to get benefits and also to give a great influence on buying decision of female consumer by television. This study aims to analyze the product placement using media television on buying decision between young female and adult female. Methodology used in this research is Independent Samples T-Test which is to compare whether two groups have different average values. This study results, the young female buy the product based on the advertisement on television that they see and make it as the recommendation, while the adult female don’t make the advertisement that they see on television as the main reason for buying the product. Keywords : product placement, advertisement, consumer buying decision